The Proces Of Making Saguer and Captikus: Proses Pembuatan Saguer dan Captikus Berbasis Animasi 3 Dimensi - RUTH WATIMENA; Arthur M. Rumagit; Sumenge T. G. Kaunang (Universitas Sam Ratulangi, 2023)
Based on the research objective, which is to create a 3D Animation-based process of making Saguer and Captikus that provides information to ease users in visualizing the manufacturing process. The 3D Animation is generated using Unity and Blender 3D applications. The researcher employs the MDLC (Multimedia Development Life Cycle) method, which consists of 6 stages. This application can be run on the Android platform. Based on the results from Q&A sessions with 20 respondents, 100% of them stated that this application is engaging and helpful in understanding and visualizing the process of making Saguer and Captikus farming. Keywords — Android, Application, 3D Animation, Multimedia Development Life Cycle, Saguer, Captikus